2019
DOI: 10.1111/sifp.12088
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Uptake of Postpartum Long‐Acting Reversible Contraception: Qualitative Study of the Perspectives of Ugandan Health Workers and Potential Clients

Abstract: Health workers have received training on delivering postpartum long-acting reversible contraceptives (LARCs) through several projects in Uganda, yet uptake still remains poor. To understand the reasons, and to gather suggestions for improving uptake, we conducted individual semi-structured interviews with a total of 80 postpartum parents, antenatal parents, health workers, and village health teams in rural south-west Uganda. Interviews were recorded, transcribed, translated, and analyzed using qualitative them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(44 citation statements)
references
References 26 publications
8
36
0
Order By: Relevance
“…A comprehensive analysis of fears, side-effects experienced and perceived barriers to the use of PPFP and LARC has been reported previously (10). There was a high level of concordance within couples regarding these fears, especially that women needed time to recover from the delivery before using contraception, particularly if they were bleeding.…”
Section: Plos Onementioning
confidence: 88%
See 1 more Smart Citation
“…A comprehensive analysis of fears, side-effects experienced and perceived barriers to the use of PPFP and LARC has been reported previously (10). There was a high level of concordance within couples regarding these fears, especially that women needed time to recover from the delivery before using contraception, particularly if they were bleeding.…”
Section: Plos Onementioning
confidence: 88%
“…An additional three couples were interviewed in the antenatal period. We also interviewed 17 health workers and 18 village health team members (VHTs), but these results are reported elsewhere (10). Eighteen focus groups were carried out in June-July 2018, (total of 173 participants), and a further 16 focus groups in February-March 2019 (150 respondents, Table 2).…”
Section: Characteristics Of Participantsmentioning
confidence: 99%
“…Also, Shahabuddin et al [34] found decision-making towards contraceptive methods use and childbearing among adolescent girls were mainly made by either their husbands or mothers-in-law especially with unemployed husbands who were financially dependent on their parents. Recently, Willcox et al [35] suggested that the traditional believes as postponing the use of contraception until complete recovery, the fear that contraceptive methods may affect the newborn and that the baby may die for any reason and so there will urgent need for getting new pregnancy are barriers to uptake of immediate postpartum contraception.…”
Section: Discussionmentioning
confidence: 99%
“…One additional article was included from the personal reference libraries of the authors. Four of the included articles were from North America [60][61][62] and Hawaii, 63 two from Nepal, 64,65 two from New Zealand, 66,67 one from Uganda 68 and one from Sri Lanka 69 (Table 1). Only four of the articles were solely adolescent-focused; IPP LARC was examined in eight studies and IPA LARC was investigated in two studies.…”
Section: Re Sultsmentioning
confidence: 99%
“…Included articles were assessed for methodologic quality using critical appraisal tools for prevalence surveys (n = 3), randomized controlled trials (n = 2), nonrandomized experimental studies (n = 1), qualitative studies (n = 3) and cross-sectional studies (n = 1). Eight studies were determined to be high-quality 60,61,[64][65][66][67][68][69] and two moderate-quality due to issues with participant recruitment, 60,63 based on methodology alone (Appendix S2). However, these assessments should not be interpreted as evidence of quality or of potential bias in the extracted data.…”
Section: Critical Appraisalmentioning
confidence: 99%